B7/CD28 in Central Tolerance: Costimulation Promotes Maturation of Regulatory T Cell Precursors and Prevents Their Clonal Deletion - Hinterberger, Maria; Wirnsberger, Gerald; Klein, Ludger (Frontiers in Immunology, 2011)
According to the “two-step model”, the intrathymic generation of CD4+ regulatory T (Treg) cells segregates into a first, T cell receptor (TCR)-driven phase and a second, cytokine dependent phase. The initial TCR stimulus gives rise to a CD25+Foxp3– developmental intermediate. These precursors subsequently require cytokine signaling to establish the mature CD25+Foxp3+ Treg cell phenotype. In addition, costimulation via CD28 / B7 (CD80/86) axis is important for the generation of a Treg cell repertoire of normal size. Recent data suggest that CD28 or B7 deficient mice lack CD25+Foxp3– Treg cell progenitors. However, these data leave open whether costimulation is also required at subsequent stages of Treg differentiation. Also, the fate of “presumptive” Treg cells carrying a permissive TCR specificity in the absence of costimulation remains to be established. Here, we have used a previously described TCR transgenic model of agonist-driven Treg differentiation in order to address these issues. Intrathymic adoptive transfer of Treg precursors indicated that costimulation is dispensable once the intermediate CD25+Foxp3– stage has been reached. Furthermore, lack of costimulation led to the physical loss of presumptive Treg cells rather than their escape from central tolerance and differentiation into the conventional CD4+ T cell lineage. Our findings suggest that CD28 signaling does not primarily operate through enhancing the TCR signal strength in order to pass the threshold intensity required to initiate Treg cell specification. Instead, costimulation seems to deliver unique and qualitatively distinct signals that coordinately foster the developmental progression of Treg precursors and prevent their negative selection.